2013
DOI: 10.1002/oby.20378
|View full text |Cite
|
Sign up to set email alerts
|

In vivo multi‐tissue efficacy of peroxisome proliferator‐activated receptor‐γ therapy on glucose and fatty acid metabolism in obese type 2 diabetic rats

Abstract: ObjectiveTo identify the disturbances in glucose and lipid metabolism observed in Type 2 Diabetes Mellitus (T2DM), we examined the interaction and contribution of multiple tissues (liver, heart, muscle, and brown adipose tissue) and monitored the effects of the PPARγ agonist rosiglitazone (RGZ) on metabolism in these tissues.Design and MethodsRates of [18F]FDG and [11C]Palmitate uptake and utilization in the Zucker Diabetic Fatty (ZDF) rat were quantified using non-invasive positron emission tomography (PET) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…A variety of proteins have been described to participate in lipid metabolism. For instance, activation of peroxisome proliferator-activated receptor (PPAR)γ can increase uptake of fatty acid in brown fat, but decrease uptake and utilization of fatty acid in liver [22] ; PPARα activation favors fatty acid oxidation in liver [23] ; leptin negatively regulates PPARγ gene expression [24] ; inhibition of protein tyrosine phosphatase-1B (PTP-1B) reduces TG accumulation in addition to improving insulin sensitivity [25] . Using ELISA, we observed that HFD group had a significant decrease in hepatic PPARγ ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of proteins have been described to participate in lipid metabolism. For instance, activation of peroxisome proliferator-activated receptor (PPAR)γ can increase uptake of fatty acid in brown fat, but decrease uptake and utilization of fatty acid in liver [22] ; PPARα activation favors fatty acid oxidation in liver [23] ; leptin negatively regulates PPARγ gene expression [24] ; inhibition of protein tyrosine phosphatase-1B (PTP-1B) reduces TG accumulation in addition to improving insulin sensitivity [25] . Using ELISA, we observed that HFD group had a significant decrease in hepatic PPARγ ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, many prior reports have linked obesity and insulin resistance with increased myocardial fatty acid uptake and utilization (6, 8, 10, 13, 26, 37, 38, 48, 49, 56 -58, 62). Furthermore, it is apparent from a number of experimental studies limiting or augmenting fatty acid uptake that the increased fatty acid uptake can contribute to impairments in myocardial function (2,22,25,28,34,44,48,50,51,59,73).…”
Section: E455 Myocardial Metabolic Flexibility In Type 2 Diabetesmentioning
confidence: 99%
“…Thiazolidindiones (TZDs), the peroxisome proliferator‐activated receptor γ (PPAR γ ) agonists, are the first insulin‐sensitive drugs that have been used to treat type 2 diabetes. Many findings support the idea that TZDs can correct the abnormalities of glucose metabolism in skeletal muscle in vivo . It has been reported that rosiglitazone (RSG), the PPAR γ agonist, ameliorates skeletal muscle insulin resistance by reducing the fat flux from adipose tissue to skeletal muscle .…”
Section: Introductionmentioning
confidence: 68%
“…Many findings support the idea that TZDs can correct the abnormalities of glucose metabolism in skeletal muscle in vivo. [16][17][18] It has been reported that rosiglitazone (RSG), the PPARγ agonist, ameliorates skeletal muscle insulin resistance by reducing the fat flux from adipose tissue to skeletal muscle. 19 In addition to insulin resistance, apoptosis is also affected by TZDs in a cell-specific manner.…”
Section: Introductionmentioning
confidence: 99%